THE INFLUENCE OF ROLE AMBIGUITY, ROLE CONFLICT, AND ROLE OVERLOAD ON EMPLOYEE CYBERLOAFING BEHAVIOR AT PT. UNITED TRACTORS, TBK MANADO BRANCH - Pricilia Natasha Kiroh; S. L. H. V. Joyce Lapian; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Employees that engage in cyberloafing avoid work stressors is by exploiting modern technologies, such internet. Work stressors are stress triggers, and workers engage in cyberloafing to avoid stress. This research was conducted to determine the influence of role ambiguity, role conflict, and role overload on employee cyberloafing behavior at PT. United Tractors, Tbk Manado Branch. This research uses a quantitative method with a questionnaire used to collect the data, Multiple Linear Regression as the tool of analysis, and 30 employees as the sample. The research results show that role ambiguity does not influence employee cyberloafing behavior, role conflict does not influence employee cyberloafing behavior, and role overload also does not influence employee cyberloafing behavior. Based on the results, it is recommended that the company and its employees can increase and maintain their understanding of responsibility for their current positions, employees can balance their duties and responsibilities as employees, and even more so pay attention to the deadline for completing tasks at work.   Keywords: role ambiguity, role conflict, role overload, cyberloafing